Motivasi Menjadi Perawat bagi Prestasi Akademik Program Sarjana (S1) Universitas Advent Indonesia - Meryli Haryati Dala Ngapa; Masta Haro (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the relationship between the motivation to become a nurse and the academic achievement of the Bachelor (S1) program at the Adventist University of Indonesia. The research method used is quantitative research with a correlation descriptive design. The results showed that the p-value between the motivation to become a nurse and GPA was 0.001 <0.05. In conclusion, there is a significant relationship between learning motivation and academic achievement in the Bachelor Program (S1) of the Adventist University of Indonesia, which has a close and positive relationship. Keywords: Motivation to Be a Nurse, Academic Achievement